2014
DOI: 10.2119/molmed.2013.00127
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Knockout of the RNA-Binding Protein HuR in CD4+ T Cells Reveals a Gene Dosage Effect on Cytokine Production

Abstract: The posttranscriptional mechanisms by which RNA binding proteins (RBPs) regulate T-cell differentiation and cytokine production in vivo remain unclear. The RBP HuR binds to labile mRNAs, usually leading to increases in mRNA stability and/or translation. Previous work demonstrated that HuR binds to the mRNAs encoding the Th2 transcription factor trans-acting T-cell-specific transcription factor (GATA-3) and Th2 cytokines interleukin (IL)-4 and IL-13, thereby regulating their expression. By using a novel conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 64 publications
0
35
0
Order By: Relevance
“…Interestingly, mice with conditional HuR deletion in a cell/tissue-specific manner are viable as observed in the GI tract (41,42), lung epithelium (43,44), brain (45), T-cells (46), and macrophages (47), and suggested that deletion of HuR in GI cancer cells would be feasible. Our findings demonstrate that PDA and CRC HuR-null cells are able to establish and grow in vitro , however, when cells become stressed with chemotoxic agents (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mice with conditional HuR deletion in a cell/tissue-specific manner are viable as observed in the GI tract (41,42), lung epithelium (43,44), brain (45), T-cells (46), and macrophages (47), and suggested that deletion of HuR in GI cancer cells would be feasible. Our findings demonstrate that PDA and CRC HuR-null cells are able to establish and grow in vitro , however, when cells become stressed with chemotoxic agents (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…HuR flox/flox mice were generated as described previously (28,51). 8 -10-week-old control (HuR flox/flox ) mice and HuR KO mice (OX40-cre HuR flox/flox ) were used.…”
Section: Animalsmentioning
confidence: 99%
“…206 • ELAVL1 HuR mouse models ELAVL1-knockout mice display embryonic lethality, thus, a number of conditional HuRknockout or conditional HuR-transgenic mice have been developed and largely for the study of the immune system. [207][208][209][210] These models have not been evaluated in cancer studies and may offer opportunities to study the effect specific immune cells as affected by HuR on cancer. It may be preferable to use the conditional knockout models as opposed to transgenic models to avoid opposite effects of HuR due to overexpression since HuR is abundantly expressed ubiquitous gene.…”
Section: • Zfp36δare Micementioning
confidence: 99%